What influences preparations of discharge documentation at patient discharge? An interview study with hospital health professionals based on the theoretical domains framework - Markiewicz, Ola Malgorzata; Menon, Aarya; Acharya, Amish; D’Lima, Danielle; Lorencatto, Fabiana; Darzi, Ara; Judah, G (BMJ open, 2025)
ObjectivesPoor quality handover instructions prepared by hospital staff have been identified as a key threat to safe discharges. To optimise patient safety, it is important to identify and understand the influences on how discharge documentation is prepared by hospital staff. The aim of this study was to systematically identify and explore important barriers and enablers to the preparation of high-quality discharge documentation by healthcare professionals (HCPs) for primary care teams at patient discharge.Setting and participantsHCPs from different staff groups (doctors, nurses, pharmacists, occupational and physiotherapists) participated in online interviews.DesignSemistructured interviews informed by the theoretical domains framework (TDF), to identify key influences on the preparation of discharge documentation. Anonymised transcripts were analysed thematically using a combined inductive-deductive approach. Themes were framed as influences on the preparation of discharge documentation. The likely importance of influences was decided through iterative team discussions structured on predetermined criteria. Criteria included whether the influence was an existing enabler, whether beliefs about the influences were expressed voluntarily and how often they were mentioned.Results12 HCPs were interviewed (5 junior doctors, 1 advanced nurse practitioner, 2 nurses, 1 occupational therapist, 1 physiotherapist and 2 pharmacists). Of 44 influences identified, 10 were deemed most important in the preparation of discharge documentation, spread across five TDF domains: knowledge (eg, lack of awareness of guidelines), skills (experience of hospital staff), social and professional role and identity (effective team communication), environmental context and resources (eg, software limitations) and social influences (eg, lack of feedback).ConclusionsThis study identified 10 important influences on how discharge documentation is prepared by hospital staff. These influences are potential targets for subsequent interventions to improve the quality of discharge documentation and patient safety during discharge.